Scope It Out: What's In and What's Out. Issue 3 (May 2017) - Price, M. Greta
Abstract : It has been nearly a year since the third edition of the Nursing Professional Development: Scope and Standards of Practice was released. During that time, many nursing professional development (NPD) departments across the nation have incorporated this foundational document into their practice. This column describes the activities of one NPD department to align their scope of practice with the NPD scope and standards and optimize their contributions to their organization.